2015
DOI: 10.1002/2015jd023438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atmospheric profiles between microwave radiometer retrievals and radiosonde soundings

Abstract: Atmospheric profiles of temperature (T), vapor density (ρv), and relative humidity (RH) retrieved from ground‐based microwave radiometer (MWR) measurements are compared with radiosonde soundings at Wuhan, China. The MWR retrievals were averaged in the ±30 min period centered at sounding times of 00 and 12 UTC. A total of 403 and 760 profiles under clear and cloudy skies were selected. Based on the comparisons, temperature profiles have better consistency than the ρv and RH profiles, lower levels are better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Many studies demonstrated that PMWR is a useful tool to sense the thermodynamic structure of the lower troposphere continuously by providing profiles of temperature and humidity with reasonable accuracy and height resolution (Ware et al, 2003(Ware et al, , 2013Xu et al, 2015). The intercomparison with the radiosonde data demonstrated the good correlation of temperature and vapour density retrievals Xu et al, 2015). The biases of temperature retrieved by PMWR against radiosondes increased with height, and the maximum bias is 4 • under 2000 m; the bias of water vapour profile was smaller than 1 g m −3 .…”
Section: Typical Haze Eventmentioning
confidence: 99%
“…Many studies demonstrated that PMWR is a useful tool to sense the thermodynamic structure of the lower troposphere continuously by providing profiles of temperature and humidity with reasonable accuracy and height resolution (Ware et al, 2003(Ware et al, , 2013Xu et al, 2015). The intercomparison with the radiosonde data demonstrated the good correlation of temperature and vapour density retrievals Xu et al, 2015). The biases of temperature retrieved by PMWR against radiosondes increased with height, and the maximum bias is 4 • under 2000 m; the bias of water vapour profile was smaller than 1 g m −3 .…”
Section: Typical Haze Eventmentioning
confidence: 99%
“…where T is the temperature measured by the microwave radiometer in K, p 0 is the reference pressure of 1013 hPa, and p is the pressure derived from the heights of a standard atmosphere (Wallace and Hobbs 2006). The pressure information is then used to estimate the mixing ratio at each level using (Stull 1988)…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…Here, we investigate the variability of the urban boundary layer in New York City using vertical profiles from three local airports, and profiles derived from a microwave radiometer within the urban centre to investigate the seasonal variabilities in the thermal and moisture boundary-layer structure. Microwave radiometers have the advantage of being robust instruments (Xu et al 2015), with a recent, extensive study judging them to be very good at estimating temperature profiles, particularly in the lower boundary layer (Lundquist et al 2017). While microwaveradiometer observations have been used to determine the mixed-layer height (Cimini et al 2013), the vertical extent of the urban heat island (Khaikine et al 2006), and for estimating stability conditions for wind-energy applications (Friedrich et al 2012), our main objectives here are to analyze the spatial variability in the thermal structure of the boundary layer over the highly dense area of New York City, and to quantify the diurnal and seasonal variabilities of the urban thermal and moisture profiles.…”
mentioning
confidence: 99%
“…Moreover, the MWR is equipped with an infrared radiation thermometer (IRT), which measures sky infrared temperature at one zenith infrared (9.6-10.5 µm) channel and gives information on cloud-base temperature (Ware et al, 2013;Cimini et al, 2015;Xu et al, 2015). Meteorological sensors attached to the MWR can obtain ambient temperature, pressure, and relative humidity at the instrument level.…”
Section: Methodsmentioning
confidence: 99%
“…Meteorological sensors attached to the MWR can obtain ambient temperature, pressure, and relative humidity at the instrument level. The retrieval algorithm developed by the factory can automatically convert the microwave, infrared, and surface meteorological measurements into temperature, humidity, and liquid profiles with the aid of neural networks (Xu et al, 2015). Longtime radiosondes and liquid water content profiles generated from radiosondes were processed within a radiative transfer model and used as the neural network training set (Ware et al, 2013).…”
Section: Methodsmentioning
confidence: 99%